Vermiremediation: Analysis of contaminated diesel in soil using Eisenia fetida and ZnO nanoparticles with cow dung - Surendrakumar, Radhakrishnan; Idhayadhulla, Akbar; Ahamed, Anis; Alodaini, Hissah Abdulrahman; Gurusamy, Raman (Frontiers in Environmental Science, 2022)
Cow dung is a valuable source of manure to improve soil quality. This study aims to enhance the soil quality by decreasing diesel contamination in the soil through the vermicomposting of cow dung and nanoparticles of ZnO. Using a powder made from cow dung, zinc ions may be easily converted into ZnO nanoparticles. To increase the quality of soil, Eisenia fetida and nanoparticles of ZnO mixed with cow dung was used. These nanoparticles were characterized by FT-IR, SEM, and TEM. The diesel impure soils were examined for 70 days by gas chromatography. Observations showed that the soil samples without the earthworms had a higher concentration of diesel than the earthworm present in the soil. In this method, diesel (4.5 ml) was reduced by almost 50% after 70 days. Diesel concentrations were significantly higher during sampling time than they were later in soil contaminated with E. fetida.